2017
DOI: 10.4103/0366-6999.201597
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Quality of Nonanesthetic Colonoscopy by Preoperative Administration of Pinaverium Bromide

Abstract: Background:Nonanesthetic colonoscopy is popular in clinical practice in China. However, intestinal spasms often result in a prolonged examination time, increased operating difficulties, decreased polyp detection rate, and failure to complete the procedure clinically. Therefore, exploring alternative approaches that can reduce the pain in patients during colonoscopy is of utmost importance, and finding the optimal preoperative administration to improve the quality of nonanesthetic colonoscopy is also necessary.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The specific pathogenesis of IBS has not been clarified clinically, and studies have shown that it may be related to brain and bowel dysfunction, gastrointestinal motility disorders, visceral hypersensitivity, psychosocial problems, and intestinal flora disorders [ 1 , 11 ]. The treatment strategy of IBS-D includes antispasmodics for abdominal pain, antidiarrhoeals, nutritional intervention, and psychotherapy, but no specific therapeutic drugs that are able to treat all the symptoms have been found [ 12 ]. Some routine pharmacotherapies (e.g., antispasmodic drugs and antidiarrheal drugs) and alternative treatments (e.g., hypnotherapy and psychotherapy) [ 13 ] have been tried but have failed to achieve the desired clinical therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The specific pathogenesis of IBS has not been clarified clinically, and studies have shown that it may be related to brain and bowel dysfunction, gastrointestinal motility disorders, visceral hypersensitivity, psychosocial problems, and intestinal flora disorders [ 1 , 11 ]. The treatment strategy of IBS-D includes antispasmodics for abdominal pain, antidiarrhoeals, nutritional intervention, and psychotherapy, but no specific therapeutic drugs that are able to treat all the symptoms have been found [ 12 ]. Some routine pharmacotherapies (e.g., antispasmodic drugs and antidiarrheal drugs) and alternative treatments (e.g., hypnotherapy and psychotherapy) [ 13 ] have been tried but have failed to achieve the desired clinical therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Another morpholinium salt, namely, pinaverium bromide has been applied as a gastrointestinal crystallizer that can inhibit the flow of calcium ions into intestinal smooth muscle cells. Based on this, the associated pinaverium bromide tablets are safely used for intestinalrelated pain [43][44][45]. Meanwhile, novel biological ingredients possessing the typical morpholinium moiety were constantly prepared and evaluated.…”
Section: Introductionmentioning
confidence: 99%